2010
DOI: 10.1163/092764410x495243
|View full text |Cite
|
Sign up to set email alerts
|

Critical Exponents of Gelation and Conductivity in Polyacrylamide Gels Doped by Multiwalled Carbon Nanotubes

Abstract: Polyacrylamide (PAM) doped by multiwalled carbon nanotube (MWNT) gels were prepared with different amounts of MWNTs varying in the range between 0.1 and 15 wt%. The PAM-MWNT composite gels were characterized by the steady state fluorescence technique (SSF). The alternative electrical conductivity (AC) of PAM-MWNT composite gels was measured by the dielectric spectroscopy technique. Observations around the gel point, t(gel) for PAM-MWNTs composite gels showed that the gel fraction exponent beta obeyed the perco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…During the gelation process, the wavelengths behave to increase to the 427 nm-peak, and decrease to the 512 nm-peak, and also the short wavelength at 380 nm shifting through 427 nm which gives the information about the interaction between the monomer, GO and pyranine as defined in the previous studies (14)(15)(16)(17)19). Because pyranine is a fluorescent probe and its photophysical properties are well characterized and can be bound to polymeric structure because of having three functional groups (20).…”
Section: Resultsmentioning
confidence: 85%
“…During the gelation process, the wavelengths behave to increase to the 427 nm-peak, and decrease to the 512 nm-peak, and also the short wavelength at 380 nm shifting through 427 nm which gives the information about the interaction between the monomer, GO and pyranine as defined in the previous studies (14)(15)(16)(17)19). Because pyranine is a fluorescent probe and its photophysical properties are well characterized and can be bound to polymeric structure because of having three functional groups (20).…”
Section: Resultsmentioning
confidence: 85%
“…However, classical results were produced at high carrageenan content (42.0%). On the other hand, PAAm-PNIPA and PAAm-MWNT composites show that the gel fraction exponent obeyed the percolation result [21,22]. In this study, the critical exponents of AAm-SA composite gels were investigated for various SA contents and it was observed that the gel fraction exponent and agree best with the percolation theory for (50.25% (w/v)) SA contents.…”
mentioning
confidence: 66%
“…By adding a luminescent dye as a probe, it is possible to measure some physical parameters of the polymerizing system, such as polarity [15,16], physical aging [17], mobility [18], and viscosity [19]. Recent studies in our laboratory, using pyranine as an intrinsic fluoroprobe, showed that the universality of composite gels could be described by classical and percolation exponents during the solgel phase transition in PAAm-kappa()-carrageenan [20], PAAm-PNIPA [21], and PAAm-multiwalled carbon nanotube composites (MWNTs) [22]. In composite hydrogels, it is found that the critical exponents did not follow the features of the same universality class, where the most important factor is the monomer content in which the exponents drastically differ from percolation to the classical values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The solution was stirred (200 rpm) for 15 min to achieve a homogenous solution. All samples were deoxygenated by bubbling nitrogen for 10 min just before the polymerization process [19] ; each pre-composite gel solution of 5 ml was poured into a cylindrical glass tube and injector for the drying experiment. Before drying was started, composites were cut into discs with a diameter of 10 mm and a thickness of 4 mm from the injector.…”
Section: Methodsmentioning
confidence: 99%